Baby-Led Introduction to SolidS (BLISS) study: a randomised controlled trial of a baby-led approach to complementary feeding. Issue 1 (December 2015) - Daniels, Lisa; Heath, Anne-Louise; Williams, Sheila; Cameron, Sonya; Fleming, Elizabeth; Taylor, Barry; Wheeler, Ben; Gibson, Rosalind; Taylor, Rachael
Abstract Background In 2002, the World Health Organization recommended that the age for starting complementary feeding should be changed from 4 to 6 months of age to 6 months. Although this change in age has generated substantial debate, surprisingly little attention has been paid to whether advice onhow to introduce complementary foods should also be changed. It has been proposed that by 6 months of age most infants will have developed sufficient motor skills to be able to feed themselves rather than needing to be spoon-fed by an adult. This has the potential to predispose infants to better growth by fostering better energy self-regulation, however no randomised controlled trials have been conducted to determine the benefits and risks of such a "baby-led" approach to complementary feeding. This is of particular interest given the widespread use of "Baby-Led Weaning" by parents internationally. Methods/Design The Baby-Led Introduction to SolidS (BLISS) study aims to assess the efficacy and acceptability of a modified version of Baby-Led Weaning that has been altered to address potential concerns with iron status, choking and growth faltering. The BLISS study will recruit 200 families from Dunedin, New Zealand, who book into the region's only maternity hospital. Parents will be randomised into an intervention (BLISS) or control group for a 12-month intervention with further follow-up at 24 months of age. Both groups will receive the standard Well Child care provided to all parents in New Zealand. The intervention group will receive additional parent contacts (n  = 8) for support and education on BLISS from before birth to 12 months of age. Outcomes of interest include body mass index at 12 months of age (primary outcome), energy self-regulation, iron and zinc intake and status, diet quality, choking, growth faltering and acceptability to parents. Discussion This study is expected to provide insight into the feasibility of a baby-led approach to complementary feeding and the extent to which this method of feeding affects infant body weight, diet quality and iron and zinc status. Results of this study will provide important information for health care professionals, parents and health policy makers. Trial registration Australian New Zealand Clinical Trials RegistryACTRN12612001133820 .